THE WAYS TO COPE THE BARRIERS ON TEACHING AND LEARNING WRITING OF THE EIGHTH YEAR STUDENTS - Novita Sumarlin Putri (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to get clear description about the teaching and learning writing in the eighth year students of a certain junior high school in Klaten. In this study, the sources of the data are events, interview with the English teacher and students, then the document such as: the syllabus, lesson plan, students’ assignments, students’ material, and photos of students’ activities. The data are result of classroom observation, interview, and the documentation of teaching and learning writing, then analysed by descriptive qualitative method. Meanwhile, the result of the study shows that teacher prepares lesson plan before teaching, plays the role as facilitator, uses quick writing and handbook as a media, gives feedback and evaluation in the end of the teaching and learning process which goes on about 90 minutes. The teacher gets some difficulties which caused by the number of students. Further, some of them do not pay attention to teacher, have lower ability, get bored, do not have handbook and dictionary. They also cannot memorize vocabulary. The teacher solves the problem by giving light punishment, using pair group discussion, writing the material in the whiteboard, being facilitator for students, encouraging the students to bring dictionary and giving correction or feedback. Keywords: case study, writing skill, teaching and learning.